Fluorophosphonate-based solid polymer electrolyte and application thereof in secondary battery
By introducing fluorophosphonate groups and urea structural units into the polymer electrolyte, the problem of flammability of traditional electrolytes is solved, and the high safety and long cycle life of lithium batteries are achieved.
Patent Information
- Application Number
- CN202411629475.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-14
AI Technical Summary
Traditional polymer electrolytes are extremely flammable and cannot effectively avoid the occurrence of thermal runaway reactions in lithium batteries, resulting in frequent safety accidents.
Fluorophosphonate-based solid polymer electrolyte is used. This electrolyte improves compatibility with the negative electrode by introducing fluorine groups and urea structural units into the polymer segment, and enhances the resistance of the material through the synergistic effect of phosphate functional groups. Fuel and electrochemical properties.
It significantly increases the starting temperature of self-extrophic heat of lithium batteries, delays the occurrence of thermal runaway reaction, reduces the maximum thermal runaway temperature inside the battery, and enhances the cycle life and thermal safety of the battery.
Smart Images

Figure CN119447442A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a polymer electrolyte, in particular to a fluorophosphonate-based solid polymer electrolyte and its application in a secondary battery (lithium / sodium battery). Background Art
[0002] In recent years, with the rapid development of my country's new energy industry, secondary batteries (such as lithium / sodium batteries) as a clean and efficient energy storage device have been widely used in mobile devices, electric vehicles, smart grids and other fields. However, in the past few years, energy storage power stations and new energy electric vehicles have repeatedly experienced safety accidents such as smoke, combustion, and explosion, which not only seriously affected personal and property safety, but also restricted the further promotion and large-scale application of lithium batteries.
[0003] Research has found that the release of heat inside lithium / sodium batteries is closely related to the electrolyte. In order to avoid the risk of thermal runaway of batteries, scientists have done a lot of research on the development of highly safe electrolytes. Among them, polymer electrolytes have shown obvious advantages in safety and preparation technology, and are one of the most effective ways to achieve highly safe lithium batteries. However, traditional polymer electrolytes are extremely flammable and still cannot avoid the occurrence of thermal runaway reactions.
[0004] There are three characteristic temperatures in the thermal runaway process of lithium batteries measured by the accelerating calorimeter, namely the self-heating starting temperature (T1), the thermal runaway (heat violent release stage) trigger temperature (T2) and the thermal runaway maximum temperature (T3). These three temperature points correspond to specific exothermic reactions / behaviors inside the lithium battery. According to these three characteristic temperatures, thermal runaway can be divided into different stages. The first stage is the induction period, during which the heat release rate inside the lithium battery is very low. The second stage is the self-heating stage, during which a series of chain exothermic reactions will occur. The heat mainly comes from the decomposition of the solid electrolyte interface (SEI), the reaction between the electrode and the electrolyte, the decomposition of the electrolyte, the phase change of the positive electrode, and the energy release of the positive and negative electrodes caused by gas crosstalk. At this stage, heat will accumulate rapidly, and when the temperature inside the battery reaches the thermal runaway trigger temperature, it will cause the battery to burn and explode. In order to further improve the safety of high-energy-density lithium batteries, polymer electrolytes can be prepared for the above-mentioned thermal runaway process to inhibit the heat release inside the battery.
[0005] Flame-retardant modification of polymer electrolytes can essentially terminate the chain exothermic reaction of secondary batteries under thermal abuse conditions. For example, the introduction of reactive flame-retardant functional groups into polymer segments can increase the self-exothermic starting temperature to a certain extent and delay the occurrence of thermal runaway reactions. It is reported that polymers containing phosphate groups are not only flame-retardant, but also can improve the compatibility of electrolytes with layered oxide positive electrodes. For example, CN107863555B discloses a flame-retardant polyphosphate solid polymer electrolyte suitable for a high-energy storage battery system, which can improve the safety of energy storage batteries to a certain extent. However, the high reactivity between the phosphate functional group and the negative electrode in the polymer affects the cycle life of high-energy storage lithium batteries (eScience, 2021, 1, 163-177). Therefore, it is necessary to develop a flame-retardant phosphonate-based polymer electrolyte with excellent safety performance and without affecting the cycle life of the battery. Summary of the invention
[0006] The object of the present invention is to provide a fluorophosphonate-based solid polymer electrolyte having excellent flame retardant effect and good electrode interface compatibility and its application in secondary batteries (lithium / sodium batteries).
[0007] To achieve the above object, the technical solution adopted by the present invention is:
[0008] A fluorophosphonate-based solid polymer electrolyte, which is obtained by in-situ polymerization of various substances in a lithium battery, wherein the various substances include monomers, metal salts, additives, and initiators, wherein the monomer is a fluorophosphonate-based monomer, or a fluorophosphonate-based monomer and other monomers; the monomer fluorophosphonate-based monomer comprises an acrylic acid derivative, a urea bond, and a fluorophosphate structural unit.
[0009] The fluorophosphonate monomer is prepared by an addition reaction of a compound containing isocyanate and acrylic acid derivative structures and a compound containing amino and fluorophosphonate structural units.
[0010] The fluorophosphonate monomer is represented by the following structural formula
[0011]
[0012] In the formula, R1 is selected from CN, halogen, C1-C6 haloalkyl, H or C1-C6 alkyl; R2 is selected from -O(CH2) x -、-NH(CH2) x -、-S(CH2) x -or-O(CH2) x O, x is an integer from 1 to 10; R3 is selected from -(CH2) y -、-NH(CH2) y -、-(CH2)y NH- or -(CH2) y O-, y is an integer of 1 to 6; R4 and R5 can be the same or different C1-C6 fluoroalkyl groups.
[0013] Preferably, in the monomer formula, R1 is selected from CN, F, C1-C6 fluoroalkyl, H or C1-C6 alkyl; R2 is selected from -O(CH2) x -、-NH(CH2) x -、-S(CH2) x -or-O(CH2) x O, x is an integer from 1 to 5; R3 is selected from -(CH2) y -、-NH(CH2) y -、-(CH2) y NH- or -(CH2) y O-, y is an integer of 1 to 6; R4 and R5 can be the same or different C1-C6 fluoroalkyl groups; wherein the fluorophosphonate monomer accounts for 10 to 100% of the mass of the polymerization system.
[0014] The other monomers are selected from polyethylene glycol methyl ether acrylate, methyl methacrylate, acrylic anhydride, acrylonitrile, ethyl isocyanate methacrylate, (n ranges from 1 to 5), One or more of the following; wherein, the mass ratio of the fluorophosphonate monomer to other monomers is (99-10):(1~90).
[0015] The solid polymer electrolyte polymerizes the following substances by mass percentage: 10% to 70% fluorophosphonate monomer or fluorophosphonate monomer and other monomers, 10% to 40% metal salt, 1% to 70% additive, 0.5% to 1% initiator, and 0% to 30% porous support material.
[0016] The metal salt is a lithium salt or a sodium salt;
[0017] The lithium salt is one or more of lithium perchlorate (LiClO4), lithium trifluoromethanesulfonate, lithium hexafluorophosphate (LiPF6), lithium difluorooxalatoborate (LiDFOB), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium bisfluorosulfonyl imide (LiFSI), lithium dioxalatoborate (LiBOB), lithium hexafluoroarsenate (LiAsF6), and lithium tetrafluoroborate (LiBF4); the sodium salt is one or more of sodium hexafluorophosphate (NaPF6), sodium perchlorate (NaClO4), sodium bistrifluoromethanesulfonyl imide (NaTFSI), sodium bisfluorosulfonyl imide (NaFSI), sodium tetrafluoroborate (NaBF4), and sodium trifluoromethanesulfonate;
[0018] The additives are succinonitrile (SN), adiponitrile (ADN), 1,3,6-hexanetrinitrile (HTCN), SiO2, ZrO2, TiO2, Al2O3, Li7La3Zr2O 12 , Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 , Li 10 GeP2S 12 , Li 14 Zn(GeO4)4、Li 5.5 LqCy 1.75 In 0.25 O 12 , LiPON, ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), fluoroethylene carbonate (FEC), ethyl methyl carbonate (EMC), methyl formate (MF), ethyl acetate (EA), ethylene glycol dimethyl ether (DME), diethylene glycol dimethyl ether (DEGDME), tetrahydrofuran (THF), one or more of sulfolane (TMS);
[0019] The initiator is one of azobisisobutyronitrile (AIBN), azobisisoheptanenitrile (ABVN), dimethyl azobisisobutyrate (AIBME), dibenzoyl peroxide (BPO), tert-butyl benzoyl peroxide (TBPB), and methyl ethyl ketone peroxide (MEKPO);
[0020] The porous supporting material is one of cellulose non-woven membrane, glass fiber, polyethylene terephthalate film (PET film), polypropylene non-woven membrane (PP), polyimide non-woven membrane, bacterial cellulose, nylon filter membrane, polytetrafluoroethylene porous membrane, and nanocellulose.
[0021] Preferably, the metal salt is LiPF6 or LiTFSI or NaPF6; the additive is SN or EC or FEC or DME; the initiator is AIBN or BPO; and the porous support material is a cellulose nonwoven membrane or glass fiber.
[0022] A method for preparing the fluorophosphonate-based solid polymer electrolyte,
[0023] (1) dissolving the metal salt in the additive according to the above ratio, and mixing them uniformly to obtain a mixture;
[0024] (2) adding a fluorophosphonate monomer or a mixture of a fluorophosphonate monomer and other monomers to the mixture;
[0025] (3) adding an initiator to the above solution and dissolving it until a uniform solution is formed;
[0026] (4) Injecting the above solution into a lithium / sodium battery containing positive and negative electrodes, and heating it at 40°C to 80°C for 6h to 12h to allow the fluorophosphonate monomer to self-polymerize in situ or the fluorophosphonate monomer to copolymerize with other monomers in situ to obtain a fluorophosphonate-based solid polymer electrolyte.
[0027] An application of the fluorophosphonate-based solid polymer electrolyte, and application of the electrolyte in lithium / sodium secondary batteries.
[0028] A lithium / sodium secondary battery comprises a positive electrode, a negative electrode and an electrolyte between the positive and negative electrodes, wherein the electrolyte is a fluorophosphonate-based solid polymer electrolyte.
[0029] A preparation method for a lithium / sodium battery. The fluorophosphonate-based solid polymer electrolyte separates the positive and negative electrode plates, seals them, and polymerizes them in situ at 40°C to 80°C to obtain a lithium / sodium battery.
[0030] The positive electrode active material may be LiFePO4, LiCoO2, LiNi x Co y Mn z O2(NCM xyz )(x+y+z=1),LiNi x Co y Al z O2(NCA xyz )(x+y+z=1), LiMn2O4, LiMnPO4, LiCoPO4, Na3V2(PO4)3, NaFePO4, NaNi 1 / 3Fe 1 / 3 Mn 1 / 3 O2, Na2MP2O7 (M=Fe, Mn, Co), Na4Fe(CN)6, etc.
[0031] The negative electrode active material can be metallic lithium, graphite, silicon carbon, silicon oxide, lithium carbonate, metallic sodium, hard carbon, soft carbon, nano silicon, etc.;
[0032] The lithium / sodium battery is a button-type battery, a soft-pack battery, a square battery or a cylindrical battery. The advantages of the present invention are:
[0033] The present invention introduces fluorine-containing groups into the polymer chain segments, improves the compatibility of the polymer electrolyte with the negative electrode, plays a role in improving the electrochemical performance of the lithium battery and delaying the self-exothermic starting temperature; at the same time, the synergistic effect with the P element can greatly increase the limiting oxygen index of the material, delay the occurrence of thermal runaway, and reduce the maximum thermal runaway temperature inside the battery; in addition, the urea structural unit contained in the polymer monomer can dissipate the mechanical stress generated by the volume deformation of the electrode and stabilize the electrode structure. Therefore, relying on the synergistic effect of the urea structure and the fluorophosphate structural unit, the prepared fluorophosphonate-based solid polymer electrolyte has important application value for improving the cycle life and thermal safety of secondary batteries.
[0034] At the same time, the solid polymer electrolyte obtained by the present invention has a simple preparation process, and the prepared polymer electrolyte has a high room temperature ionic conductivity (1×10 -4 S / cm~9×10 -3 S / cm), a wide electrochemical window (greater than 4V); when used in secondary batteries, it can form a protective layer containing inorganic components such as fluorine and nitrogen on the positive and negative electrodes, which can not only improve the cycle performance of the battery, but also delay the occurrence of thermal runaway reactions, thus buying more escape time for people. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 The electrochemical window of the fluorophosphonate-based solid polymer electrolyte prepared in Example 1.
[0036] Figure 2 The flammability test of the fluorophosphonate-based solid polymer electrolyte prepared in Example 2 was performed.
[0037] Figure 3 The long cycle performance of the lithium battery assembled in Example 3 at room temperature and 0.5C.
[0038] Figure 4 The long cycle performance of the sodium battery assembled in Example 4 at 0.5C at room temperature.
[0039] Figure 5 This is a curve obtained by testing the lithium battery assembled in Example 5 using an accelerating calorimeter. DETAILED DESCRIPTION
[0040] The specific implementation modes of the present invention are further described below in conjunction with examples. It should be noted that the specific implementation modes described here are only for illustrating and explaining the present invention, and are not limited to the present invention.
[0041] Example 1
[0042] Prepare LiTFSI / SN solution in a glove box filled with argon, add LiDFOB after stirring and dissolving, and set aside after it is completely dissolved. (Depend on The fluorophosphonate monomer and methyl methacrylate shown in the above solution are dissolved together, and the initiator AIBN is added. The uniform solution obtained after complete dissolution is injected into a lithium battery containing positive and negative electrode materials, and placed at 80°C for in-situ polymerization. After 8 hours, the desired in-situ polymerized solid electrolyte is obtained.
[0043] The raw material ratios used to prepare the solid electrolyte are shown in Table 1. The ionic conductivity of the prepared polymer electrolyte was obtained by electrochemical impedance spectroscopy. The electrolyte was assembled into a stainless steel / stainless steel button cell. The room temperature ionic conductivity of the electrolyte measured by an electrochemical workstation was 1.2×10 -3 S cm -1 In addition, the prepared polymer electrolyte was assembled into a stainless steel / lithium metal battery, and the electrolyte initial decomposition voltage measured by linear sweep voltammetry was 5.1 V ( Figure 1 shown).
[0044] Table 1:
[0045]
[0046] Example 2
[0047] Prepare NaTFSI / EC solution in a glove box filled with argon and stir until it dissolves and set aside. The fluorophosphonate monomer shown is dissolved in a NaTFSI / EC solution, and an initiator BPO is added. The uniform solution obtained after complete dissolution is injected into a sodium battery containing positive and negative electrode materials, and placed at 60°C for in-situ polymerization. After 8 hours, the desired in-situ polymerized solid electrolyte is obtained.
[0048] The raw material ratios used to prepare the solid electrolyte are shown in Table 2. The room temperature ionic conductivity of the prepared electrolyte is 3.4×10 -3 S cm -1 , the initial decomposition voltage is 4.4 V. In addition, the polymer electrolyte does not burn after nine ignitions, showing non-flammability (such as Figure 2 In addition, the soft-pack battery assembled with the polymer electrolyte did not burn or explode after being subjected to extrusion and needle puncture tests.
[0049] Table 2:
[0050]
[0051] Example 3
[0052] Prepare LiPF6 / EC-DEC solution in a glove box filled with argon and stir until it dissolves and set aside. The fluorophosphonate monomer and ethyl isocyanate methacrylate shown are dissolved together in a LiPF6 / EC-DEC solution, and an initiator AIBN is added. The uniform solution obtained after complete dissolution is injected into a lithium battery containing positive and negative electrode materials, and placed at 60°C for in-situ polymerization. After 10 hours, the desired in-situ polymerized solid electrolyte is obtained.
[0053] The raw material ratios used to prepare the solid electrolyte are shown in Table 3. The room temperature ionic conductivity of the prepared solid electrolyte is 7.8×10 -3 S cm -1 The initial decomposition voltage is 5.2V. The NCM811 / graphite full battery was assembled using the above electrolyte and the charge and discharge test was carried out at an operating voltage of 3.0-4.3V and 0.5C. The capacity retention rate of the assembled full battery after 100 cycles was 91% (as shown in Figure 2). Figure 3 As shown in the figure, it shows excellent long cycle performance. In addition, the NCM811 / graphite soft pack battery assembled with the polymer electrolyte did not burn or explode after the needle puncture test.
[0054] Table 3:
[0055]
[0056] Example 4
[0057] Prepare NaPF6 / FEC-DEC solution in a glove box filled with argon, and stir until it dissolves and set aside. The fluorophosphonate monomer shown is dissolved in a NaPF6 / FEC-DEC solution, and an initiator BPO is added. The uniform solution obtained after complete dissolution is injected into a sodium battery containing positive and negative electrode materials, and placed at 50°C for in-situ polymerization. After 12 hours, the desired in-situ polymerized solid electrolyte is obtained.
[0058] The raw material ratios used to prepare the solid electrolyte are shown in Table 4. The room temperature ionic conductivity of the prepared solid electrolyte is 5.5×10 -3 S cm -1 The initial decomposition voltage is 4.5 V. 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 / hard carbon full battery, charge and discharge test at working voltage 3.0 ~ 4.0V and 0.5C. After 100 cycles, the capacity retention rate of the assembled full battery was 94% (such as Figure 4 As shown in the figure, it shows excellent long-cycle performance. In addition, the soft-pack battery assembled with the polymer electrolyte did not burn or explode after the extrusion test.
[0059] Table 4:
[0060]
[0061] Example 5
[0062] Prepare LiDFOB / PC solution in a glove box filled with argon and stir until it dissolves and then set aside. The fluorophosphonate monomer and acrylic anhydride shown are dissolved together in a LiDFOB / PC solution, and an initiator AIBN is added. The uniform solution obtained after complete dissolution is injected into a lithium battery containing positive and negative electrode materials, and placed at 70°C for in-situ polymerization. After 10 hours, the desired in-situ polymerized solid electrolyte is obtained.
[0063] The raw material ratios used to prepare the solid electrolyte are shown in Table 5. The room temperature ionic conductivity of the prepared solid electrolyte is 2.0×10 -3 S cm -1 The initial decomposition voltage is 5.2V. The LiCoO2 / graphite soft pack battery assembled using the above electrolyte can be stably cycled. In addition, the soft pack battery was tested by an accelerated calorimeter. The test results show that (such as Figure 5 As shown in Figure 2, the addition of fluorophosphonate-based polymer increased T1 from 78°C to 105°C and delayed the occurrence of thermal runaway of lithium batteries. In addition, the addition of the polymer also reduced the maximum temperature of thermal runaway of lithium batteries (from 438°C to 357°C).
[0064] Table 5:
[0065]
[0066] Example 6
[0067] Prepare LiFSI / FEC solution in a glove box filled with argon and stir until it dissolves and then set aside. The fluorophosphonate monomers shown and They are dissolved together in LiFSI / FEC solution, and the initiator AIBME is added. The uniform solution obtained after complete dissolution is injected into a lithium battery containing positive and negative electrode materials, and placed at 70°C for in-situ polymerization. After 8 hours, the required in-situ polymerized solid electrolyte is obtained.
[0068] The raw material ratios used to prepare the solid electrolyte are shown in Table 6. The room temperature ionic conductivity of the prepared solid electrolyte is 2.5×10 -3 S cm -1, the initial decomposition voltage is 5.2 V. In addition, the microcalorimeter test shows that the addition of polymer can reduce the total heat release of the electrolyte (from 35.2 kJ / g to 29.8 kJ / g) and the heat release rate (from 412 J / gK to 386 J / gK), proving that fluorophosphonate-based polymers can improve the flame retardancy of the electrolyte.
[0069] Table 6
[0070]
[0071] Example 7
[0072] Prepare LiBOB / DME solution in a glove box filled with argon and stir until it dissolves and then set aside. The fluorophosphonate monomer shown is dissolved in a LiBOB / DME solution, and an initiator ABVN is added. The uniform solution obtained after complete dissolution is injected into a lithium battery containing positive and negative electrode materials, and placed at 40° C. for in-situ polymerization. After 15 hours, the desired in-situ polymerized solid electrolyte is obtained.
[0073] The raw material ratios used to prepare the solid electrolyte are shown in Table 7. The room temperature lithium ion conductivity of the prepared solid electrolyte is 0.5×10 -3 S cm -1 , the initial decomposition voltage is 5.0 V. In addition, the polymer electrolyte does not burn after ignition for 47 seconds, showing non-flammability.
[0074] Table 7:
[0075]
[0076] Example 8
[0077] Prepare NaClO4 / EMC solution in a glove box filled with argon and stir until it dissolves and then set aside. The fluorophosphonate monomers shown and Dissolve them together in NaClO4 / EMC solution, add inorganic particles SiO2, stir thoroughly and add initiator AIBME. The uniform solution obtained after the above solution is completely dissolved is injected into the sodium battery containing positive and negative electrode materials, placed at 80℃ for in-situ polymerization, and the required in-situ polymerized solid electrolyte is obtained after 7 hours.
[0078] The raw material ratio for preparing the solid electrolyte is shown in Table 8. The room temperature sodium ion conductivity of the prepared solid electrolyte is 1.7×10 -3 S cm -1, the initial decomposition voltage is 4.5V. The Na3V2(PO4)3 / Na metal battery assembled using the polymer electrolyte can be stably cycled at a voltage of 2.0-4.0V. In addition, the battery was subjected to an accelerated calorimeter test. The test results show that the addition of fluorophosphonate-based polymers increases T1 and T2 from 100°C and 150°C to 110°C and 163°C, respectively, and delays the occurrence of thermal runaway of lithium batteries.
[0079] Table 8
[0080]
Claims
1. A fluorophosphonate-based solid polymer electrolyte, characterized in that : The solid polymer electrolyte is obtained by in-situ polymerization of various substances in a lithium battery, and the various substances include monomers, metal salts, additives, and initiators, wherein the monomer is a fluorophosphonate monomer, or a fluorophosphonate monomer and other monomers; the monomer fluorophosphonate monomer contains acrylic acid derivatives, urea bonds, and fluorophosphate structural units.
2. The fluorophosphonate-based solid polymer electrolyte according to claim 1, characterized in that: The fluorophosphonate monomer is represented by the following structural formula In the formula, R1 is selected from CN, halogen, C1-C6 haloalkyl, H or C1-C6 alkyl; R2 is selected from -O(CH2) x -、-NH(CH2) x -、-S(CH2) x -or-O(CH2) x O, x is an integer from 1 to 10; R3 is selected from -(CH2) y -、-NH(CH2) y -、-(CH2) y NH- or -(CH2) y O-, y is an integer of 1 to 6; R4, R5 can be the same or different and selected from C1-C6 fluoroalkyl.
3. The fluorophosphonate-based solid polymer electrolyte according to claim 1, characterized in that: The other monomers are selected from polyethylene glycol methyl ether acrylate, methyl methacrylate, acrylic anhydride, acrylonitrile, ethyl isocyanate methacrylate, (n ranges from 1 to 5), One or more of the following; wherein the mass ratio of the fluorophosphonate monomer to other monomers is (99-10):(1-90).
4. The fluorophosphonate-based solid polymer electrolyte according to any one of claims 1 to 3, characterized in that: The solid polymer electrolyte polymer components are calculated by mass percentage, including 10% to 70% fluorophosphonate monomers or fluorophosphonate monomers and other monomers, 10% to 40% metal salts, 1% to 70% additives, 0.5% to 1% initiators, and 0% to 30% porous support materials.
5. The fluorophosphonate-based solid polymer electrolyte according to claim 4, characterized in that: The metal salt is a lithium salt or a sodium salt; The additives are succinonitrile (SN), adiponitrile (ADN), 1,3,6-hexanetrinitrile (HTCN), SiO2, ZrO2, TiO2, Al2O3, Li7La3Zr2O 12 , Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 , Li 10 GeP2S 12 , Li 14 Zn(GeO4)4、Li 5.5 LqCy 1.75 In 0.25 O 12 , LiPON, ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), fluoroethylene carbonate (FEC), ethyl methyl carbonate (EMC), methyl formate (MF), ethyl acetate (EA), ethylene glycol dimethyl ether (DME), diethylene glycol dimethyl ether (DEGDME), tetrahydrofuran (THF), one or more of sulfolane (TMS); The initiator is one of azobisisobutyronitrile (AIBN), azobisisoheptanenitrile (ABVN), dimethyl azobisisobutyrate (AIBME), dibenzoyl peroxide (BPO), tert-butyl benzoyl peroxide (TBPB), and methyl ethyl ketone peroxide (MEKPO); The porous supporting material is one of cellulose non-woven membrane, glass fiber, polyethylene terephthalate film (PET film), polypropylene non-woven membrane (PP), polyimide non-woven membrane, bacterial cellulose, nylon filter membrane, polytetrafluoroethylene porous membrane, and nanocellulose.
6. A method for preparing the fluorophosphonate-based solid polymer electrolyte according to claim 1, characterized in that (1) dissolving the metal salt in the additive according to the above ratio, and mixing them uniformly to obtain a mixture; (2) adding a fluorophosphonate monomer or a mixture of a fluorophosphonate monomer and other monomers to the mixture; (3) adding an initiator to the above solution and dissolving it until a uniform solution is formed; (4) Injecting the above solution into a lithium / sodium battery containing positive and negative electrodes, and heating it at 40°C to 80°C for 6h to 12h to allow the fluorophosphonate monomer to self-polymerize in situ or the fluorophosphonate monomer to copolymerize with other monomers in situ to obtain a fluorophosphonate-based solid polymer electrolyte.
7. An application of the fluorophosphonate-based solid polymer electrolyte according to claim 1, characterized in that: Application of the electrolyte in lithium / sodium secondary batteries.
8. A lithium / sodium secondary battery, comprising a positive electrode, a negative electrode, and an electrolyte between the positive and negative electrodes, characterized in that: The electrolyte is the fluorophosphonate-based solid polymer electrolyte according to claim 1.
9. The lithium / sodium secondary battery according to claim 8, characterized in that: The lithium / sodium battery model is a button battery, a soft-pack battery, a square battery or a cylindrical battery.
Citation Information
Patent Citations
A non-flammable solid polymer electrolyte and its application in solid-state secondary batteries
CN107863555B
Cited By
Flame-retardant double-salt polymer solid electrolyte as well as preparation method and application thereof
CN120376736A